Disease Characteristics and Treatments Associated with Outcome in Primary Angiitis of the Central Nervous System—A Multicenter Cohort Study in 163 Patients - Fisse, Anna Lena; Bonberg, Nadine; Beuker, Carolin; Pfeuffer, Claudia; Heidenreich, Andreas; Krüger, Christina; Deb-Chatterji, Milani; Becker, Jana; Gerner, Stefan; Küpper, Clemens; Nitsch, Louisa; Kestner, Roxane Isabelle; et al. (Annals of Neurology, 2025)
Objective: The aim was to determine patient, disease, and treatment characteristics associated with outcome in patients with primary angiitis of the central nervous system (PACNS) in a large multicenter German cohort. Methods: In a retrospective, observational cohort study, we analyzed 163 adult patients who met the diagnostic criteria for PACNS. Data were collected from January 2004 to December 2018 in 13 tertiary care centers in Germany. Survival, recurrence-free survival and long-term global disability were assessed. Results: Of 163 patients with PACNS (median [interquartile range (IQR)] age 48 [39–59.5] years; 73 [45%] women), 29 (18%) died, 84 (52%) had a poor outcome (modified Rankin scale [mRS] 3–6 at last follow-up), and 82 (50%) patients relapsed. Poorer survival was associated with patient age (hazard ratio [HR], 1.96 [95% confidence interval (CI), 1.41–2.74] per 10 years), longer time between initial manifestation and diagnosis (HR, 1.01 [95% CI, 1.00–1.01] per month), and necrotizing subtype (HR, 10.2 [95% CI, 2.18–48.2]). Long-term disability was associated with older age (odds ratio [OR], 1.40 [95% CI, 1.07–1.86] per 10 years), and worse mRS score at diagnosis (OR, 4.43 [95% CI, 1.97–10.4]). Patients treated with cyclophosphamide alone or in combination with steroids had a lower incidence of relapse than untreated patients (HR, 0.44 [95% CI, 0.22–0.86]; HR, 0.47 [95% CI, 0.24–0.92]). Interpretation: In patients with PACNS, the long-term outcome depends on several patient and disease characteristics. Our results favor treatment with cyclophosphamide alone or in combination with steroids, because this was associated with a reduction in the relapse rate. ANN NEUROL 2025.
CRIS-Team Scopus Importer:2025-07-04